Sexual Equality in an Integrated Europe - Elman, R. author. aut Link
XX, 206 p.
Keywords: This book examines the role of 'Europe' in defining, maintaining, constructing, and remedying sex discrimination. The author investigates the origins, institutions, and policies associated with recent European Union efforts to stem violence against women, sex trafficking, racism, and heterosexism.